2020
DOI: 10.1116/1.5140602
|View full text |Cite
|
Sign up to set email alerts
|

Field emission microscopy of carbon nanotube fibers: Evaluating and interpreting spatial emission

Abstract: In this work, we quantify field emission properties of cathodes made from carbon nanotube (CNT) fibers. The cathodes were arranged in different configurations to determine the effect of cathode geometry on the emission properties. Various geometries were investigated including: 1) flat cut fiber tip, 2) folded fiber, 3) looped fiber and 4) and fibers wound around a cylinder. We employ a custom field emission microscope to quantify I-V characteristics in combination with laterallyresolved field-dependent electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
0
28
0
2
Order By: Relevance
“…This sample was formed by braiding and twisting 90 µm fibers, then folding the resulting yarn multiple times and inserting it in a metal tube. 2 Scanning electron microscopy (SEM) images of the samples are given in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This sample was formed by braiding and twisting 90 µm fibers, then folding the resulting yarn multiple times and inserting it in a metal tube. 2 Scanning electron microscopy (SEM) images of the samples are given in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies [1][2][3][4][5][6] have convincingly demonstrated that the electron emission from a large surface area field emission cathode placed in a macroscopic electric field E is not uniform. The emission area is only a small portion of the total surface area of a cathode since most of the emission is confined to a small number of emission spots randomly distributed over the cathode surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a number of physical mechanisms at play and this is currently a subject of intense research. Thus, a routine searching for a knee point was developed based on an earlier idea implemented for dc case 6 . It is included as an optional data processing tool.…”
Section: Determining Fowler-nordheim Parametersmentioning
confidence: 99%
“…Many studies [1][2][3][4][5][6] have convincingly demonstrated that electron emission from a large surface area field emission cathode placed in a macroscopic electric field E is not uniform. The area contributing to emission is only a small portion of the total surface area available for emission.…”
Section: Introductionmentioning
confidence: 99%